Enantioselective pharmacokinetics and cardiovascular effects of nebivolol in L-NAME hypertensive rats - Bertera, Facundo Martin (2014)
The cardiovascular effects and pharmacokinetics of nebivolol were assessed in N(G)-nitro-l-arginine methyl ester (L-NAME) hypertensive and normotensive control rats. Male Wistar rats were randomly divided to drink tap water (control) or L-NAME solution for 2 weeks. The effects of nebivolol (3 or 10 mg kg−1 i.v.) on blood pressure (BP), heart rate and BP variability (BPV) were recorded in awake L-NAME and control rats. Short-term and beat-to-beat BPV was assessed by the s.d. and spectral analysis of the BP recordings. Nebivolol pharmacokinetics was studied by means of traditional blood sampling. Nebivolol showed enantioselective pharmacokinetics in both experimental groups; the clearance and the volume of distribution of l-nebivolol were significantly greater than those of the d-enantiomer. The hypotensive response to nebivolol was significantly enhanced in L-NAME rats (Δmean arterial pressure (MAP): −16.1±1.1%, P<0.05 vs. control rats) compared with normotensive animals (ΔMAP: −1.4±2.1%). An analysis of the beat-to-beat BPV showed a greater reduction in VLF BPV in the L-NAME compare with the control rats. Nebivolol significantly reduced the low-frequency/high-frequency ratio in hypertensive L-NAME animals compared with normotensive rats. Short-term BPV was markedly reduced by nebivolol in both experimental groups, although the attenuation of the s.d. of BP recording was greater in L-NAME rats. In conclusion, the hypotensive efficacy of nebivolol is significantly enhanced in L-NAME rats compared with normotensive animals, which is most likely due to a greater reduction in vascular sympathetic activity. Nebivolol markedly attenuated short-term BPV in both experimental groups, suggesting that β-blockers with additional pharmacological actions provide beneficial cardiovascular effects by controlling high BP and its short-term variability.